Ursula Tr¸per, The Invisible Woman: Zara Schmelen, African Mission Assistant at the Cape and in Namaland : Unacknowledged Mission Heroes (Historia, 2021)
At the age of thirteen, the author of this book, living in Germany, discovered that she had an African ancestor, who had been married to her great-great-great grandfather, the missionary Johann Heinrich Schmelen, who had worked for the London Missionary Society (LMS) in what is now Namibia and the Northern Cape in the early nineteenth century.